A novel contrast-induced acute kidney injury mouse model based on low-osmolar contrast medium - Jiajia Wu; Jianxiao Shen; Wanpeng Wang; Na Jiang; Haijiao Jin; Xiajing Che; Zhaohui Ni; Yan Fang; Shan Mou (Renal Failure, 2022)
The contrast-induced acute kidney injury (CI-AKI) has been becoming the third common cause of hospital-acquired acute kidney injury. An ideal animal model is essential for understanding the pathophysiology of CI-AKI. Previous CI-AKI studies were mostly performed on rats with high-osmolar contrast medium (HOCM), which is unsuitable for transgenic researches. This study provides a novel, efficient and reproducible CI-AKI model which was developed in mouse by administrating a low-osmolar contrast medium (LOCM). First of all, we applied the frequently used pretreatments (uninephrectomy and water deprivation), which combined with HOCM on rats could induce CI-AKI, on mice with LOCM. Secondly, we attempted to find a novel pretreatment suitable for mouse and LOCM by combining two classic pretreatments(uninephrectomy, water deprivation and furosemide administration). Finally, we evaluate the kidney damage of the novel model. We found that this mouse model possessed a significant reduction in renal function, severe renal tissue damage, and increased renal tubular cells apoptosis, indicating that LOCM is a feasible inducer for CI-AKI mice model. Taken together, we found that uninephrectomy (UPHT) combined with 24 h water deprivation and furosemide administration 20 min before LOCM (iohexol, 10 ml/kg) application is a feasible pretreatment to establish a novel CI-AKI mouse model.